2016
DOI: 10.4266/kjccm.2016.00171
|View full text |Cite
|
Sign up to set email alerts
|

Delta Neutrophil Index as a Prognostic Marker in the Pediatric Intensive Care Unit

Abstract: Background: The immature granulocyte count has been reported to be a marker of infection and sepsis. The difference in leukocyte subfractions (delta neutrophil index, DNI) in ADVIA 2120 reflects the fraction of circulating immature granulocytes in the blood. This study evaluated the clinical utility of DNI as a severity and prediction marker in critically ill patients with sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 20 publications
2
5
0
Order By: Relevance
“…found that in paediatric intensive care unit(PICU) patients, as the admission DNI level increased, the ICU scoring system values also increased, and the proportion of survivors decreased. The DNI at PICU admission was also positively correlated with ICU scores, lactate and CRP levels and negatively correlated with platelet counts 15 . Similarly, we found the highest DNI value in sepsis patients in our study.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…found that in paediatric intensive care unit(PICU) patients, as the admission DNI level increased, the ICU scoring system values also increased, and the proportion of survivors decreased. The DNI at PICU admission was also positively correlated with ICU scores, lactate and CRP levels and negatively correlated with platelet counts 15 . Similarly, we found the highest DNI value in sepsis patients in our study.…”
Section: Discussionsupporting
confidence: 83%
“…The DNI at PICU admission was also positively correlated with ICU scores, lactate and CRP levels and negatively correlated with platelet counts. 15 Similarly, we found the highest DNI value in sepsis patients in our study.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Delta neutrophil index (DNI) is a hematological inflammatory marker that reflects the fraction of IGs in the circulating blood. While several studies 8,9 have demonstrated a relationship between increased levels of DNI and inflammation/infection in adults and children, only a few studies have assessed the relationship between DNI level and sepsis in neonates. 10,11 We hypothesized that there may be a marked increase in DNI in response to bacterial infection in neonates, similar to that seen in adults.…”
Section: Introductionmentioning
confidence: 99%